2020
DOI: 10.3762/bjnano.11.6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat treatment on the morphology and mobility of Au nanoparticles

Abstract: In the present paper, we investigate the effect of heat treatment on the geometry and mobility of Au nanoparticles (NPs) on a Si substrate. Chemically synthesized Au NPs of diameter ranging from 5 to 27 nm were annealed at 200, 400, 600 and 800 °C for 1 h. A change in the geometry from faceted to more rounded shapes were observed with increasing annealing temperature. Kinetic Monte Carlo simulations indicate that the NPs become rounded due to the minimization of the surface area and the transition to lower ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The absence of gold outside the nanoparticles, according to the EDX results for the background, indicated that the gold nanoparticles were obtained in a quantitative yield. The conditions for clustering the gold NPs were recently studied [ 66 ] and it was shown that heating the gold NPs at a very high temperature (800 °C) yielded NPs with a pentagonal symmetry [ 67 ]. In this work a very similar structure was obtained, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of gold outside the nanoparticles, according to the EDX results for the background, indicated that the gold nanoparticles were obtained in a quantitative yield. The conditions for clustering the gold NPs were recently studied [ 66 ] and it was shown that heating the gold NPs at a very high temperature (800 °C) yielded NPs with a pentagonal symmetry [ 67 ]. In this work a very similar structure was obtained, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the adhesion and static friction of metal nanostructures decrease significantly after annealing due to the rounding and decreasing of the contact area with the substrate [27]. The atomic force microscopy (AFM) manipulation approach can be successfully applied to probe the adhesion/static friction magnitude and to estimate the fraction of movable NPs [28], which, for example, can be displaced or washed away during the drop-casting of the investigated chemical solution due to capillary forces. This understanding becomes critical when examining techniques like heat-induced nanowire (NW) fragmentation, which could potentially be used for creating SERS substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In practical applications, the diameters of Ag NWs are typically significantly larger. However, during prolonged heat treatment (lasting minutes or more), surface atom diffusion can lead to morphological changes in NWs even at temperatures several hundred degrees below the melting point of the material [ 26 27 ]. Sintering of Ag and Au NWs at intersections can occur at temperatures as low as 125–200 °C within minutes [ 27 28 ].…”
Section: Introductionmentioning
confidence: 99%